Critical transitions in the shape morphing of kirigami metallic glass. (20th January 2021) - Han, D.X.; Zhao, L.; Chen, S.H.; Wang, G.; Chan, K.C.
Abstract: Kirigami, the ancient Japanese paper cutting technique, has been applied to achieve high stretchability and low energy loss of designed metallic glass. Despite the exploration of the underlying deformation mechanism of kirigami-inspired structures from the energy point of view, the morphable responses of the kirigami patterns and the origin of the kirigami response are yet to be fully understood. This study reveals the mechanical driven-forms of the kirigami structure with the corresponding deformation stages. Based on the beam deflection theory, the elastic buckling behavior of kirigami metallic glass is manifested and a critical force prediction model is developed. Moreover, a force concentration parameter is introduced in the rigid-plastic deformation stage, predicting the nominal ultimate force. The kirigami-inspired facture force is firstly proposed. The findings of these models are in good agreement with the experimental size-dependent kirigami responses, and expected to provide significant insights into the understanding of the deformation behavior and the design of kirigami metallic glasses.